PERAN KEPUASAN PELANGGAN DALAM MEMEDIASI KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN - Ananda, I Putu Satya Nitya; Jatra, I Made (E-Jurnal Manajemen; Vol 8 No 11 (2019)DO - 10.24843/EJMUNUD.2019.v08.i11.p20, 2019)
Nitya Home Stay is one of the lodgings that have nuances of villas on Nusa Lembongan Island, Nusa Penida, Klungkung, Bali. Nitya Home Stay has many competitors who are in Nusa Lembongan. The many inns that exist on Nusa Lembongan make competition so tight. Every company competes to provide the best offer in order to attract customers from competitors. In order to survive in the increasingly fierce competition, Nitya Home Stay must be able to provide maximum service quality so that customers feel satisfied and will have an impact on customer loyalty. This study aims to determine the role of customer satisfaction in mediating service quality to customer loyalty. This research was conducted in Nusa Lembongan, using 125 respondents. This study uses data analysis techniques in the form of Path Analysis. The results of this study indicate that service quality has a positive and significant effect on customer customer satisfaction and loyalty. Customer satisfaction has a positive and significant effect on customer loyalty. Customer satisfaction is positively and significantly mediates service quality towards customer loyalty. Nitya Home Stay needs to continue to improve the quality of service so that customers feel satisfied so as to create customer loyalty. Keywords: service quality, customer satisfaction, customer loyalty